17β-estradiol at low concentrations attenuates the efficacy of tamoxifen in breast cancer therapy. (December 2019) - Xu, Zhixiang; Zheng, Xianyao; Xia, Xueshan; Wang, Xiaoxia; Luo, Nao; Huang, Bin; Pan, Xuejun
Abstract: Tamoxifen has been applied widely in the treatment of estrogen receptor (ER)-positive breast cancer. The impact of low concentrations of 17β-estradiol (E2) (a pervasive environmental pollutant) on its effectiveness was studied in vitro using an MCF-7 cell line. Cell proliferation, migration, invasion, and apoptosis were studied along with cell cycle progression, reactive oxygen species generation and mitochondrial membrane potentials repression. The signaling pathways involved were identified. Typical concentrations of E2 in the environment (10 −10 to 10 −8  M) were observed to promote cell growth and protect MCF-7 cells from tamoxifen's cytotoxicity. Cell migration, invasion, cell cycle progression and apoptosis all involved in reducing tamoxifen's cytotoxicity. E2 at environmental concentrations induced PI3K/Akt and MAPK/ERK signal transduction through the estrogen receptor pathways to affect cell proliferation. Taken together, the results explain how E2 in the environment may attenuate the efficacy of tamoxifen in ER-positive breast cancer therapy. They provide considerable support for E2's adverse effects on human health and cancer management. Graphical abstract: Image 1 Highlights: Low concentrations of 17β-estradiol promote cell growth by influencing cell metastasis, cycle progression and apoptosis. Tamoxifen induces cell apoptosis through the p53 signaling cascade regulated by reactive oxygen species. 17β-estradiol at low concentrations partially counteracts tamoxifen-induced cell apoptosis. 17β-estradiol at low concentrations activates PI3K/Akt and MAPK/ERK signaling transduction. Estrogen receptors in both the nucleus and the cell membrane are involved in 17β-estradiol's effects. Abstract : Tamoxifen-induced cytotoxicity is partially counteracted when 17β-estradiol is present at low concentrations typical of its presence as an environmental pollutant.